Five Novel Genes Related to the Pathogenesis and Progression of Pancreatic Neuroendocrine Tumors by Bioinformatics Analysis With RT-qPCR Verification - Xiao, Yu; Yang, Yuemei; Wang, Yanfeng; Li, Xiaoou; Wang, Wenze (Frontiers in Neuroscience, 2019)
Objective: To explore novel related genes and potential biomarkers of pancreatic neuroendocrine tumors (PanNETs). Materials and methods: 2 data sets from ICGC and 2 from NCBI GEO database were used to identify the differentially expressed genes (DEGs) in PanNETs. The common DEGs among the 4 sources were analyzed, furthermore, the relationship of these gene expression patterns with different PanNETs grades, their mutation status and corresponding impact on prognosis, the interaction network, and the relationship with 3 known PanNETs genes (ATRX, DAXX, MEN1) were analyzed by 2 other GEO data and cBioPortal database. Finally, the expressions of novel DEGs were validated in Chinese PanNETs tissues by RT-qPCR. Results: 5 new DEGs (ABCC8, PCSK2, IL13RA2, KLKB1 and PART1) and 1 confirmed DEG-ISL1 were identified. The mutation counts of DEGs increased with the tumor grade increasing from G1 to G3, and PanNETs patients present vascular invasion or deceased. These DEGs expression patterns in PanNETs are quite different from that of pancreatic ductal adenocarcinoma, and are related with A-D-M (ATRX-DAXX-MEN1) mutation. ABCC8 and KLKB1 are co-occurrence with A-D-M axis in PanNETs. Importantly, patients with DEG mutations have a lower survival rate. RT-qPCR verification results of KLKB1 (P<0.01), IL13RA2 (P<0.01), ABCC8 (P<0.01) and PART1 (P<0.0001) expressions in Chinese PanNETs tissues are consistent with our database analysis, which were significantly up-regulated . However, the expression of PCSK2 (P<0.01) was contrary to our bioinformatics analysis, which was significantly down-regulated, suggesting the expression trend of PCSK2 may be different among different races. These results indicated that these 5 genes may play an important role in the occurrence and progression of PanNETs Conclusion: 5 novel common DEGs identified are related to the development and prognosis of PanNETs and may serve as specific biomarkers and therapeutic targets.